REGENERASI TANAMAN KERKLILY {Lilium longiflorum Thunb.) MELALUI EMBRIOGENESIS SOMATIK PADA EKSPLAN DAUN - Priyono, Priyono (BERITA BIOLOGI, 2001)
The effects of plant growth regulators on somatic embryo genesis in Lilium longiflorum Thunb.leaf cultures were studied.The aim of the research is to study the regeneration ofi. longiflorum via somatic embryogenesis of leaf explant.IAAat5 level of concentrations (0-1 mg/1) combined with BAP at 4 level of concentrations (0-2 mg/1) were tested to induction of somatic embryogenesis in the first stage. Combination of two cytokinins, namely BAP and kinetin, combined with either of four auxins, namely IAA, IBA, NAA or 2,4D were tested to induce the somatic embryo genesis in the second stage. Combination of two concentrations of ABA, namely 0 and 1 mg/1 combined with 5 level concentrations of GA3, namely 0, 0.25, 0.5, 0.75 and 1 mg/1 were tested to improve the somatic embryos maturation.The results showed that somatic embryos were promoted by addition of IAA and BAP. The study of auxin and cytokinin combinations on somatic embryogenesis showed that somatic embryogenesis of kerk lily induced by addition of auxin and cytokinin in the culture medium.The maximum somatic embryo induction was obtained on medium contained of 0.25 mg/1 IAA combined with 1 mg/1 kinetin. Somatic embryos maturation were improved by transferring the somatic embryo from induction medium to maturation medium that contained 0.5 mg/I GA3 +1 mg/1 ABA.